Kansas and the santa fe trail - Smith, George Wildman (My University, 1893)
Introduction: Less than a century ago, Kansas was included in what was then known as the Great American Desert, and as such, was inhabited only by the wild forms of animal life, and was ruled over and roamed over by the Indians.
Citation: Smith, George Wildman. Kansas and the santa fe trail. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Kansas; Great American desert; Indians; Theses; Manuscripts (documents)